Bony fish bycatch in the southern Brazil pink shrimp (Farfantepenaeus brasiliensis and F. paulensis) fishery - Vianna,Marcelo (2005)
Trawling for pink shrimp (Farfantepenaeus brasiliensis and F. paulensis) catches also large quantities of fish, mostly bony fish, which are discarded, as they have no commercial value. Their composition and abundance were studied in an area that corresponded to the southeastern coastline of Brazil. Ninety one species were registered. Incidental fishing affected mainly small individuals and occured throughout the year. The year round rate of bony fish to shrimp catches was 10,5:1,0. Three assemblages of bony fishes could be identified, influenced by the seasonal variation of the water masses, the predominant group being associated with the Coastal Water, another with the penetration of colder waters onto the platform (SACW) and a third group of a more homogenous distribution. The most critical period identified for the bycatch capture was the beginning of the winter, which was due to the overlapping of fish assemblages and the peak of fishing recruitment.